Factors associated with adherence to follow-up calls in cancer patients receiving care at a community oncology practice. (July 2021) - Monestime, Shanada; Page, Ray; Shaw, Nicole; Martin, Randy; Jordan, William; Rangel, Jessica; Aryal, Subhash
Background: Follow-up calls in the oncology setting are frequently used to augment care and encourage oral antineoplastic adherence. However, limited data are available on patient populations that would benefit from this intervention versus populations that may require alternative interventions. The purpose of this study was to identify characteristics among patients on oral antineoplastic agents that influence their likelihood to respond to follow-up calls. Methods: Patients receiving care from one of the eight community oncology clinics within the same branch were analyzed. Patients were included if they were ≥18 years, received a new oral antineoplastic agent that was electronically prescribed between August 2018–October 2018, and picked up their first fill from their pharmacy of choice. Patients received up to six follow-up calls after picking up their first prescription. Calls were categorized as adherent (≥3 monthly interactions) or non-adherent (<3 monthly interactions). Logistic regression models were used to evaluate factors associated with follow-up call adherence. Factors included demographics, cancer stage, marital status, employment, pharmacy setting (internal pharmacy versus external pharmacy), and insurance used by the patient. Descriptive analysis was performed to analyze response rates, cancer diagnosis, and to determine the best time and day patients responded to follow-up calls. Results: Data from 125 patients were analyzed, of which 65 patients (52%) were adherent to follow-up calls and the mean response rate over six months was 45% (range: 35% – 54%). High success rates for follow-up calls were seen between 12–3 pm and on Tuesdays and Thursdays. After adjusting for covariates, patients with stage III-IV were 89% less likely to respond to follow-up calls compared to those with stage 0-II (95% CI: 0.02–0.64; p = 0.01), patients with commercial insurance were 79% less likely to adhere to follow-up calls compared to those on government insurance (95% CI: 0.06-0.71; p = 0.01), and patients using an external pharmacy had a 2.8 times increase odds of being adherent (95% CI 0.98-8.34; p = 0.05). All other factors were not significant. Conclusions: For patients taking oral antineoplastics, non-adherence to follow-up calls was observed in more than 45% of patients receiving care from a community oncology clinic. Findings demonstrated that those with advanced stages of cancer, on commercial insurance, and going to an internal pharmacy were at higher risk for not adhering to follow up calls. Therefore, alternative methods for managing adherence and side effects in these populations are warranted.